Mental health and productivity at work: does what you do matter? - Cobb-Clark, Deborah A.; Bubonya, Melisa; Wooden, Mark (My University, 2017)
Much of the economic cost of mental illness stems from workers’ reduced productivity. Using nationally representative panel data we analyze the links between mental health and two alternative workplace productivity measures – absenteeism and presenteeism (i.e., lower productivity while attending work) – explicitly allowing these relationships to be moderated by the nature of the job itself. We find that absence rates are approximately five percent higher among workers who report being in poor mental health. Moreover, job conditions are related to both presenteeism and absenteeism even after accounting for workers’ self-reported mental health status. Job conditions are relatively more important in understanding diminished productivity at work if workers are in good rather than poor mental health. The effects of job complexity and stress on absenteeism do not depend on workers’ mental health, while job security and control moderate the effect of mental illness on absence days.
Labour Economics
Keywords: Health and wellbeing; Labour market